2011
DOI: 10.1111/j.1540-8167.2011.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Cervical and Lumbar Spondylosis in Interventional Electrophysiologists

Abstract: There is a significant increased prevalence of cervical spondylosis among interventional electrophysiologists. Programs to improve ergonomics and minimize time spent wearing lead are needed. The same vigilance that is used to ensure radiation safety in the laboratory should be applied to create ergonomic safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…Brain tumors, breast cancer in female cardiologists, and cataracts have been reported in interventional cardiologists and staff potentially due to their increased radiation exposure 49–51 . In addition, a higher prevalence of orthopedic injuries have been reported in interventional cardiologists, who wear lead apparel to protect themselves from radiation, compared to noninterventional cardiologists 52 . Studies indicate that over one‐third of interventional cardiologists with spinal complaints miss work due to spine problems 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…Brain tumors, breast cancer in female cardiologists, and cataracts have been reported in interventional cardiologists and staff potentially due to their increased radiation exposure 49–51 . In addition, a higher prevalence of orthopedic injuries have been reported in interventional cardiologists, who wear lead apparel to protect themselves from radiation, compared to noninterventional cardiologists 52 . Studies indicate that over one‐third of interventional cardiologists with spinal complaints miss work due to spine problems 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…Though radiation‐shielding equipment such as lead aprons and collars have been shown to reduce the rate of exposure in radial catheterization procedures, the electrophysiologists’ hands are exposed to radiation inevitably . Besides, some studies have reported that the prevalence of cervical and lumbar spondylosis increased significantly among interventional electrophysiologists due to the heavy lead equipments . Hence, it is urgent to take measures to reduce radiation exposure and minimize time spent wearing lead as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The vest/skirt configuration is preferred by many operators to reduce the risk of musculoskeletal/back injury (75)(76)(77). This wraparound style is typically 0.25-mm lead-equivalent, overlapping anteriorly, so that, when worn, the double thickness anteriorly provides 0.5-mm lead equivalence.…”
Section: Use Personal Protective Garments/shieldingmentioning
confidence: 99%